Resin composition, method for producing resin composition, pellet, molded body, injection molded body and equipment
Patent Information
- Application Number
- JP2024130700
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-10-13
- Filing Date
- 2024-08-07
- Publication Date
- 2025-02-27
AI Technical Summary
【0006】 本実施形態によれば、優れた力学特性を有する樹脂組成物を提供することが出来る。
Smart Images

Figure 2025027453000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition. [Background technology]
[0002] Mechanical properties can be controlled by adding fillers and elastomers to thermoplastic resins. Patent Document 1 discloses a method in which melt-kneading is performed twice to unevenly distribute fillers and elastomers in a thermoplastic resin in order to improve impact strength (toughness) and elastic modulus (rigidity). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2020-193284 A Summary of the Invention [Problem to be solved by the invention]
[0004] There is room for improvement in mechanical properties of the resin composition disclosed in Patent Document 1. Therefore, one aspect of the present embodiment is aimed at providing a resin composition having excellent mechanical properties. [Means for solving the problem]
[0005] The resin composition of the present invention comprises A resin composition comprising a matrix mainly composed of a polar polymer, a plurality of filler particles mainly composed of an inorganic material and having a particle diameter of 0.1 μm or more, and a plurality of elastomer particles each having a particle diameter of 0.1 μm or more, the plurality of filler particles and the plurality of elastomer particles are in contact with the matrix and dispersed in the matrix, In a cross section of the resin composition, a first elastomer particle and a second elastomer particle among the plurality of elastomer particles are present at an interval of 10 μm or less, Among the plurality of filler particles, a first filler particle that is closest to the first elastomer particle in the cross section is separated from the first elastomer particle via the matrix, The second filler particle among the plurality of filler particles that is closest to the second elastomer particle in the cross section is separated from the second elastomer particle via the matrix. Effect of the Invention
[0006] According to this embodiment, a resin composition having excellent mechanical properties can be provided. [Brief description of the drawings]
[0007] [Figure 1] FIG. 2 is a schematic diagram illustrating the morphology of a resin composition. [Diagram 2] FIG. 2 is a schematic diagram illustrating the morphology of a resin composition. [Diagram 3] FIG. 2 is a schematic diagram illustrating the occurrence of cracks in a molded product obtained by molding a resin composition. [Figure 4] FIG. 2 is a schematic diagram illustrating the device. [Diagram 5] 1 shows cross-sectional SEM images of Example 1 and Comparative Example 1. [Figure 6] 1 is a cross-sectional SEM image of Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] ≪Resin composition≫ The resin composition according to this embodiment will be described in detail. FIG. 1 is a schematic diagram illustrating the morphology of the resin composition according to this embodiment. FIG. 1(a) shows the morphology of a resin composition 10 according to this embodiment, and FIG. 1(b) shows the morphology of a comparative resin composition 20. In FIG. 1, 1 is a matrix, 2 is filler particles, 3 is elastomer particles, and 4 is an elastomer material.
[0009] As shown in FIG. 1( a ), a resin composition 10 of this embodiment contains a matrix 1 , a plurality of filler particles 2 , and a plurality of elastomer particles 3 .
[0010] The main component of the matrix 1 is a polar polymer. Therefore, the matrix 1 mainly composed of a resin can be called a matrix resin or a resin matrix. The main component of the plurality of filler particles 2 is an inorganic material. The filler particles 2 mainly composed of an inorganic material can be called inorganic filler particles. The main component of the plurality of elastomer particles 3 is typically an organic material, but may be an inorganic material. The elastomer particles 3 mainly composed of an organic material can be called organic elastomer particles. In the matrix 1 mainly composed of a polar polymer, the mass of the polar polymer as the main component is the largest, and the mass of the polar polymer as the main component in the matrix 1 is preferably 50 mass% or more, more preferably 75 mass% or more, and even more preferably 90 mass% or more. The matrix 1 mainly composed of a polar polymer may contain a subcomponent in addition to the main component which is a polar polymer, and this subcomponent does not have to be a polar polymer.
[0011] Since the particle diameter of the plurality of filler particles 2 of interest is 0.1 μm or more, the resin composition 10 includes a plurality of filler particles 2 having a particle diameter of 0.1 μm or more. The resin composition 10 may or may not include a plurality of filler particles having a particle diameter of less than 0.1 μm. Since the particle diameter of the plurality of elastomer particles 3 of interest is 0.1 μm or more, the resin composition 10 includes a plurality of elastomer particles 3 having a particle diameter of 0.1 μm or more. The resin composition 10 may or may not include a plurality of elastomer particles having a particle diameter of less than 0.1 μm. The particle diameter of the filler particles 2 or elastomer particles 3 of interest is 0.1 μm or more because particles having a particle diameter of 0.1 μm or more greatly contribute to the control of mechanical properties.
[0012] When the filler particles 2 have a short diameter and a long diameter, the short diameter can be used as the particle diameter of the filler particles 2. The aspect ratio of the filler particles 2 is defined as the ratio of the long diameter to the short diameter (long diameter / short diameter). When the aspect ratio of the filler particles 2 is less than 5, it can be classified as a low aspect ratio, and when the aspect ratio of the filler particles 2 is 5 or more, it can be classified as a high aspect ratio.
[0013] A plurality of filler particles 2 and a plurality of elastomer particles 3 are dispersed in a matrix 1. It is preferable that the plurality of filler particles 2 and the plurality of elastomer particles 3 are each dispersed independently in the matrix 1, and this dispersion structure is called an independent dispersion structure. In the independent dispersion structure, the plurality of filler particles 2 and the plurality of elastomer particles 3 are in contact with the matrix 1.
[0014] As shown in FIG. 1(a), in the resin composition 10 of this embodiment, the filler particles 2 and the elastomer particles 3 have an independent dispersion structure in which they are independently dispersed in the matrix 1. In a cross-section of the resin composition 10, the first elastomer particles 3a and the second elastomer particles 3b of the plurality of elastomer particles 3 are spaced apart from each other by less than 100 μm. That is, the distance between the first elastomer particles 3a and the second elastomer particles 3b is less than 100 μm. In a cross-section of the resin composition 10, the first elastomer particles 3a and the second elastomer particles 3b of the plurality of elastomer particles 3 are spaced apart from each other by less than 10 μm. That is, the distance between the first elastomer particles 3a and the second elastomer particles 3b is less than 10 μm. The first elastomer particle 3a and the second elastomer particle 3b here can be selected as two elastomer particles 3 of interest among the multiple elastomer particles 3. That is, the condition for the two elastomer particles 3 of interest is that the distance between the two elastomer particles is less than 100 μm, or even 10 μm or less. In this embodiment, the first elastomer particle 3a and the second elastomer particle 3b that exist close to each other in this manner have an independent dispersion structure. The second elastomer particle 3b may be an elastomer particle that exists closest to the first elastomer particle 3a among the multiple elastomer particles 3, or, instead, there may be another elastomer particle that is located closer to the first elastomer particle 3a than the second elastomer particle 3b. It is not essential that any other elastomer particle 3 exists within a range of 10 μm around any elastomer particle 3. For example, focusing on two elastomer particles 3 that are spaced apart by 100 μm or more is not very suitable for evaluating the independent dispersion structure, and even more so, focusing on two elastomer particles that are extremely spaced apart by 1 mm or more is not appropriate.The plurality of elastomer particles 3 may include two closest elastomer particles 3 with a distance of more than 10 μm, but such two elastomer particles 3 do not need to be selected as a pair of a first elastomer particle 3a and a second elastomer particle 3b to be focused on for evaluating the independent dispersion structure. The distance between the first elastomer particle 3a and the second elastomer particle 3b is preferably 0.1 μm or more, more preferably 1 μm or more. This is because elastomer particles 3a and 3b that are extremely close to each other are not very suitable for evaluating dispersibility.
[0015] In the resin composition 10 having an independent dispersion structure, the first filler particle 2a, which is present among the plurality of filler particles 2 and is closest to the first elastomer particle 3a in the observed cross section, is separated from the first elastomer particle 3a via the matrix 1. In the resin composition 10 having an independent dispersion structure, the first elastomer particle 3a is separated from the first filler particle 2a, which is present among the plurality of filler particles 2 and is closest to the first elastomer particle 3a in the observed cross section, via the matrix 1. That is, the first filler particle 2a is not in contact with the first elastomer particle 3a, and the matrix 1 is interposed between the first filler particle 2a and the first elastomer particle 3a. In other words, the first filler particle 2a and the first elastomer particle 3a are separated from each other by the matrix 1.
[0016] In addition, in the resin composition 10 having an independent dispersion structure, the second filler particle 2b, which is present among the plurality of filler particles 2 and is closest to the second elastomer particle 3b in the observation cross section, is separated from the second elastomer particle 3b via the matrix 1. In the resin composition 10 having an independent dispersion structure, the second elastomer particle 3b is separated from the second filler particle 2b, which is present among the plurality of filler particles 2 and is closest to the second elastomer particle 3b in the observation cross section, via the matrix 1. That is, the second filler particle 2b is not in contact with the second elastomer particle 3b, and the matrix 1 is interposed between the second filler particle 2b and the second elastomer particle 3b. In other words, the second filler particle 2b and the second elastomer particle 3b are separated from each other by the matrix 1.
[0017] On the other hand, as shown in Fig. 1(b), in the comparative resin composition 20, the filler particles 2 are incorporated into the elastomer material 4, forming a core-shell structure. In the resin composition 20 having a core-shell structure, the filler particles 2 are in contact with the elastomer material 4 and are not separated. Moreover, in the resin composition 20 having a core-shell structure shown in Fig. 1(b), the filler particles 2 are not in contact with the matrix 1.
[0018] The resin composition of the present embodiment has an independent dispersion structure as shown in FIG. 1(a), and thus can have excellent mechanical properties, such as flexural modulus and impact strength.
[0019] The distance between the first filler particles 2a and the second filler particles 2b may be less than 100 μm. The distance between the first filler particles 2a and the second filler particles 2b is preferably 10 μm or less. In this embodiment, it is preferable that the first filler particles 2a and the second filler particles 2b, which are present close to each other in this manner, have an independent dispersion structure.
[0020] The distance between the first filler particle 2a and the first elastomer particle 3a may be less than 100 μm. The distance between the first filler particle 2a and the first elastomer particle 3a is preferably 10 μm or less. The distance between the second filler particle 2b and the second elastomer particle 3b may also be less than 100 μm. It is also preferable that the distance between the second filler particle 2b and the second elastomer particle 3b is 10 μm or less. In this way, the distance between the nearest filler particle 2 and the nearest elastomer particle 3 is small, so that excellent mechanical properties can be obtained. The distance between the first filler particle 2a and the first elastomer particle 3a is, for example, 10 nm or more, and may be 0.1 μm or more. The distance between the second filler particle 2b and the second elastomer particle 3b is, for example, 10 nm or more, and may be 0.1 μm or more.
[0021] 10 of the observed cross section of the resin composition 10 2 μm 2 X% by number of 10 or more filler particles 2 in the above area range are separated from a plurality of elastomer particles 3 via the matrix 1. 2 μm 2 X number % of 10 or more filler particles 2 in the above area range is present in the matrix phase 1. X (number %) is, for example, a majority of 50% by number or more, preferably 70% by number or more, more preferably 80% by number or more, and even more preferably 90% by number or more.
[0022] 10 of the observed cross section of the resin composition 10 2 μm 2 Y number % of 10 or more elastomer particles 3 in the above area range are separated from a plurality of filler particles 2 via the matrix 1. 2 μm 2In the above area range, 10 or more elastomer particles 3 are present in the matrix phase 1 at a number Y %. Y (number %) is, for example, a majority of 50% by number or more, preferably 70% by number or more, more preferably 80% by number or more, and even more preferably 90% by number or more.
[0023] 10 of the observed cross section of the above-mentioned resin composition 10 2 μm 2 It is preferable that the above-mentioned first elastomer particles 3a, second elastomer particles 3b, first filler particles 2a, and second filler particles 2b are included in the above area range. 2 μm 2 The occupancy rate of the matrix 1 in the above area range is preferably 30 area % or more and 90 area % or less. 2 μm 2 The occupancy rate of the plurality of filler particles 2 in the above area range is preferably 1 area % or more and 50 area % or less. 2 μm 2 The occupancy rate of the above area range is preferably 1 area % or more and 50 area % or less of the plurality of elastomer particles 3. The lower limit of the area range of the observed cross section of the resin composition 10 described above is 10 2 μm 2 However, the upper limit may be set as long as the number of filler particles 2 or the number of elastomer particles 3 is within a range in which 10 or more particles are included and the number of particles can be calculated within a reasonable time. For example, the area of the observed cross section of the resin composition 10 is 1000 2 μm 2 Less than or equal to 500 2 μm 2 It is preferable that the value is equal to or less than 250. 2 μm 2 More preferably, it is 130 2 μm 2 In particular, if the filler particle 2 has a low aspect ratio, the area of the observed cross section is preferably 250 or less. 2 μm 2 More preferably, it is 130 2 μm 2In particular, if the filler particle 2 has a high aspect ratio, the area of the observed cross section is preferably 130 or less. 2 μm 2 More preferably, it is 250 or more. 2 μm 2 It is also preferable that the area of the resin composition 10 is equal to or less than the width of the square. The outline of the area of the observed cross section of the resin composition 10 may be a square, a rectangle, or a circle, for example, a square of 1000 μm×1000 μm, a square of 100 μm×100 μm, or a square of 10 μm×10 μm, but the maximum width of the area is 2000 μm or less, preferably 500 μm or less, preferably 250 μm or less, and also preferably 200 μm or less. The maximum width of the area of the 100 μm×100 μm square is the diagonal (√2)×100 μm. In addition, it is preferable that 30 area % or more of the region 1 μm from the outer periphery of the filler particle 2 is occupied by the matrix 1.
[0024] Resin composition 10, 100 3 μm 3 More than 1mm 3 In the composition in the following volume range, the matrix 1 is preferably 30 mass % or more and 90 mass % or less. 3 μm 3 More than 1mm 3 In the composition in the following volume range, the plurality of filler particles 2 are preferably 1% by mass or more and 50% by mass or less. 3 μm 3 More than 1mm 3In the composition in the following volume range, the elastomer material constituting the plurality of elastomer particles 3 is preferably 1% by mass or more and 50% by mass or less. This volume range preferably includes the above-mentioned first elastomer particles 3a, second elastomer particles 3b, first filler particles 2a, and second filler particles 2b. The contour of the volume range of the resin composition 10 may be a cube, a rectangular parallelepiped, or a sphere, for example, a 100 μm×100 μm×100 μm cube or a 1 mm×1 mm×1 mm cube, but the maximum width of the volume range is preferably 2 mm or less, more preferably 1 mm or less. The maximum width of the volume range of a 1 mm×1 mm×1 mm rectangular parallelepiped is the diagonal (√3)×1 mm.
[0025] <Matrix 1> As the matrix, polar polymers are used among thermoplastic resins. Polar polymers are polymers that contain polar groups, such as amide groups, imide groups, carbonyl groups (ketone groups), and ester bonds, in the main chain. Polar polymers are generally resins called general-purpose engineering plastics or super engineering plastics, and are used in applications that require higher physical properties, such as heat resistance and strength, than general-purpose resins such as polyethylene and polypropylene. In addition, if it becomes possible to improve the mechanical properties, it will be possible to make molded products thinner and lighter, so further improvements in the physical properties of polar polymers are expected.
[0026] Specific examples of polar polymers include polymers having an amide group, such as polyamide and polyamideimide. Polymers having an imide group, such as polyimide, polyamideimide, and polyetherimide. Polymers having a carbonyl group (ketone group), such as polyetherketone and polyetheretherketone. Polymers having an ester bond, such as polyarylate, polycarbonate, and polyester. Polyesters include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and polybutylene naphthalate.
[0027] Among thermoplastic resins, it is preferable to use a crystalline polymer as the matrix. The crystalline polymer is advantageous in that it is superior in hardness, elasticity, and rigidity compared to amorphous polymers. Among the above-mentioned polar polymers, examples of the crystalline polymer include polyamide, polyether ketone, polyether ether ketone, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and polybutylene naphthalate. Among polyesters, polyarylate and polycarbonate are amorphous polymers. As the polar polymer, polyester is preferable, and polyethylene terephthalate is more preferable. Since the amount of CO2 emitted during the production of polyethylene terephthalate is smaller than the amount of CO2 emitted during the production of polycarbonate, the use of polyethylene terephthalate can contribute to reducing CO2 emissions. The crystallinity of the matrix or crystalline polymer is, for example, 1 to 50%, and preferably 1 to 40%. The crystallinity can be controlled by the molding conditions (temperature and pressure).
[0028] The matrix may also be a polar polymer crosslinked using a crosslinking agent. Examples of the crosslinking agent include compounds that undergo a crosslinking reaction due to heat, such as carbodiimide crosslinking agents, oxazoline crosslinking agents, epoxy crosslinking agents, and isocyanate crosslinking agents. The polar polymer may also be a recycled polymer, for example, obtained by recovering used polymers with reduced molecular weights and recrosslinking the used polymers with a crosslinking agent to increase the molecular weight. As the used polymer and the recycled polymer, polyethylene terephthalate, which is produced and used in large quantities, is suitable.
[0029] The carbodiimide crosslinking agent in this embodiment is a compound having at least one carbodiimide group in the molecule, and can be produced, for example, by heating an organic isocyanate in the presence of a suitable catalyst and subjecting it to a decarboxylation reaction. The carbodiimide group is represented by (-N=C=N-). In a resin matrix in which a carbodiimide crosslinking agent is used, the carbodiimide group derived from the carbodiimide crosslinking agent exists as a part of the polymer.
[0030] Examples of carbodiimide crosslinking agents include diphenylcarbodiimide, dicyclohexylcarbodiimide, di-2,6-dimethylphenylcarbodiimide, diisopropylcarbodiimide, dioctyldecylcarbodiimide, di-o-toluylcarbodiimide, di-p-toluylcarbodiimide, di-p-nitrophenylcarbodiimide, di-p-aminophenylcarbodiimide, di-p-hydroxyphenylcarbodiimide, di-p-chlorophenylcarbodiimide, di-o-chlorophenylcarbodiimide, di-3,4-dichlorophenylcarbodiimide, Nylcarbodiimide, di-2,5-dichlorophenylcarbodiimide, p-phenylene-bis-o-tolylcarbodiimide, p-phenylene-bis-dicyclohexylcarbodiimide, p-phenylene-bis-di-p-chlorophenylcarbodiimide, 2,6,2',6'-tetraisopropyldiphenylcarbodiimide, hexamethylene-bis-cyclohexylcarbodiimide, ethylene-bis-diphenylcarbodiimide, ethylene-bis-di-cyclohexylcarbodiimide, N,N'-di-o-triylcarbodiimide, N,N'-di Phenylcarbodiimide, N,N'-dioctyldecylcarbodiimide, N,N'-di-2,6-dimethylphenylcarbodiimide, N-triyl-N'-cyclohexylcarbodiimide, N,N'-di-2,6-diisopropylphenylcarbodiimide, N,N'-di-2,6-di-tert-butylphenylcarbodiimide, N-toluyl-N'-phenylcarbodiimide, N,N'-di-p-nitrophenylcarbodiimide, N,N'-di-p-aminophenylcarbodiimide, N,N'-di-p-hydroxyphenylcarbodiimide, N,N'-di-cyclohexylcarbodiimide, N,N'-di-p-tolylcarbodiimide, N,N'-benzylcarbodiimide, N-octadecyl-N'-phenylcarbodiimide, N-benzyl-N'-phenylcarbodiimide, N-octadecyl-N'-tolylcarbodiimide, N-cyclohexyl-N'-tolylcarbodiimide, N-phenyl-N'-tolylcarbodiimide, N-benzyl-N'-tolylcarbodiimide, N,N'-di-o-ethylphenylcarbodiimide, N,N'-di-p-ethylphenylcarbodiimide, N,Mono- or dicarbodiimide compounds such as N'-di-o-isopropylphenylcarbodiimide, N,N'-di-p-isopropylphenylcarbodiimide, N,N'-di-o-isobutylphenylcarbodiimide, N,N'-di-p-isobutylphenylcarbodiimide, N,N'-di-2,6-diethylphenylcarbodiimide, N,N'-di-2-ethyl-6-isopropylphenylcarbodiimide, N,N'-di-2-isobutyl-6-isopropylphenylcarbodiimide, N,N'-di-2,4,6-trimethylphenylcarbodiimide, N,N'-di-2,4,6-triisopropylphenylcarbodiimide, and N,N'-di-2,4,6-triisobutylphenylcarbodiimide; poly(1,6-hexamethylene carbodiimide); Examples of polycarbodiimides include poly(4,4'-methylenebiscyclohexylcarbodiimide), poly(1,3-cyclohexylenecarbodiimide), poly(1,4-cyclohexylenecarbodiimide), poly(4,4'-diphenylmethanecarbodiimide), poly(3,3'-dimethyl-4,4'-diphenylmethanecarbodiimide), poly(naphthylenecarbodiimide), poly(p-phenylenecarbodiimide), poly(m-phenylenecarbodiimide), poly(tolylcarbodiimide), poly(diisopropylcarbodiimide), poly(methyl-diisopropylphenylenecarbodiimide), poly(triethylphenylenecarbodiimide), and poly(triisopropylphenylenecarbodiimide).
[0031] The oxazoline crosslinking agent in this embodiment is a compound having an oxazoline group in the molecule. In particular, a polymer synthesized using a monomer containing an oxazoline compound as at least one of the raw monomers is preferred. The oxazoline compound includes 2-oxazoline, 3-oxazoline, and 4-oxazoline compounds, and any of them may be used, but 2-oxazoline compounds are particularly reactive and have been put into practical industrial use. Examples of oxazoline compounds include 2-vinyl-2-oxazoline, 5-methyl-2-vinyl-2-oxazoline, 4,4-oxazoline, 4,4-dimethyl-2-vinyl-5,6-dihydro-4H-1,-oxazine, 4,4,6-trimethyl-2-vinyl-5,6-dihydro-4H-1,3-oxazine, 2-isopropenyl-2-oxazoline, 4,4-dimethyl-2-isopropenyl-2-oxazoline, 4-acryloyl-oxymethyl-2,4-dimethyl 4-Methacryloyl-oxymethyl-2,4-dimethyl-2-oxazoline, 4-methacryloyl-oxymethyl-2-phenyl-4-methyl-2-oxazoline, 2-(4-vinylphenyl)-4,4-dimethyl-2-oxazoline, 4-ethyl-4-hydroxymethyl-2-isopropenyl-2-oxazoline, 4-ethyl-4-carboethoxymethyl-2-isopropenyl-2-oxazoline, and the like, but are not limited thereto.
[0032] In the present embodiment, for example, a glycidyl ether compound, a glycidyl ester compound, a glycidyl amine compound, a glycidyl imide compound, an alicyclic epoxy compound, or the like can be preferably used as the epoxy-based crosslinking agent.
[0033] Examples of the glycidyl ether compound include, for example, butyl glycidyl ether, stearyl glycidyl ether, allyl glycidyl ether, phenyl glycidyl ether, o-phenylphenyl glycidyl ether, ethylene oxide lauric alcohol glycidyl ether, ethylene oxide phenol glycidyl ether, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, polytetramethylene glycol diglycidyl ether, Examples of the epoxy resins include bisphenol A diglycidyl ether type epoxy resins, bisphenol F diglycidyl ether type epoxy resins, and bisphenol S diglycidyl ether type epoxy resins obtained by condensation reaction of bisphenols such as bisphenol A, cyclohexanedimethanol diglycidyl ether, glycerol triglycidyl ether, trimethylolpropane triglycidyl ether, pentaerythritol polyglycidyl ether, 2,2-bis-(4-hydroxyphenyl)propane, 2,2-bis-(4-hydroxyphenyl)methane, and bis(4-hydroxyphenyl)sulfone with epichlorohydrin. Among these, bisphenol A diglycidyl ether type epoxy resins are preferred.
[0034] Examples of the glycidyl ester compound include benzoic acid glycidyl ester, p-toluic acid glycidyl ester, cyclohexane carboxylic acid glycidyl ester, stearic acid glycidyl ester, lauric acid glycidyl ester, palmitic acid glycidyl ester, versatic acid glycidyl ester, oleic acid glycidyl ester, linoleic acid glycidyl ester, linolenic acid glycidyl ester, terephthalic acid diglycidyl ester, isophthalic acid diglycidyl ester, phthalic acid diglycidyl ester, naphthalenedicarboxylic acid diglycidyl ester, and the like. Examples of the glycidyl ester include glycidyl ester of benzoic acid, diglycidyl ester of methyl terephthalic acid, diglycidyl ester of hexahydrophthalic acid, diglycidyl ester of tetrahydrophthalic acid, diglycidyl ester of cyclohexanedicarboxylic acid, diglycidyl ester of adipic acid, diglycidyl ester of succinic acid, diglycidyl ester of sebacic acid, diglycidyl ester of dodecanedioic acid, diglycidyl ester of octadecanedicarboxylic acid, triglycidyl ester of trimellitic acid, and tetraglycidyl ester of pyromellitic acid. Among these, glycidyl ester of benzoic acid and glycidyl ester of versatic acid are preferred.
[0035] Examples of the glycidyl amine compound include tetraglycidylaminodiphenylmethane, triglycidyl-paraaminophenol, triglycidyl-metaaminophenol, diglycidyl aniline, diglycidyl toluidine, tetraglycidyl metaxylenediamine, diglycidyl tribromoaniline, tetraglycidyl bisaminomethylcyclohexane, triglycidyl cyanurate, and triglycidyl isocyanurate. Examples of the glycidyl imide compound include N-glycidyl phthalimide, N-glycidyl-4-methylphthalimide, N-glycidyl-4,5-dimethylphthalimide, N-glycidyl-3-methylphthalimide, N-glycidyl-3,6-dimethylphthalimide, N-glycidyl-4-ethoxyphthalimide, N-glycidyl-4-chlorophthalimide, N-glycidyl-4,5-dichlorophthalimide, N-glycidyl-3,4,5,6-tetrabromophthalimide, and N-glycidyl-4-n-butyl-5- Examples of such phthalimide include bromophthalimide, N-glycidyl succinimide, N-glycidyl hexahydrophthalimide, N-glycidyl-1,2,3,6-tetrahydrophthalimide, N-glycidyl maleimide, N-glycidyl-α,β-dimethylsuccinimide, N-glycidyl-α-ethylsuccinimide, N-glycidyl-α-propylsuccinimide, N-glycidyl benzamide, N-glycidyl-p-methylbenzamide, N-glycidyl naphthamide, and N-glycidyl steramide. Of these, N-glycidyl phthalimide is preferred.
[0036] Examples of the alicyclic epoxy compound include 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, bis(3,4-epoxycyclohexylmethyl)adipate, vinylcyclohexene diepoxide, N-methyl-4,5-epoxycyclohexane-1,2-dicarboxylic acid imide, N-ethyl-4,5-epoxycyclohexane-1,2-dicarboxylic acid imide, N-phenyl-4,5-epoxycyclohexane-1,2-dicarboxylic acid imide, N-naphthyl-4,5-epoxycyclohexane-1,2-dicarboxylic acid imide, and N-tolyl-3-methyl-4,5-epoxycyclohexane-1,2-dicarboxylic acid imide.
[0037] Other epoxy compounds that can be used include epoxy-modified fatty acid glycerides such as epoxidized soybean oil, epoxidized linseed oil, and epoxidized whale oil, phenol novolac type epoxy resins, and cresol nosolac type epoxy resins.
[0038] The isocyanate crosslinking agent used in the present embodiment is not particularly limited as long as it has an isocyanate group as a functional group in the compound, and a known polyisocyanate crosslinking agent can be used. Specifically, a commonly used water-dispersible polyisocyanate crosslinking agent can be used. A water-dispersible polyisocyanate crosslinking agent is a polyisocyanate polymer having a hydrophilic group introduced therein, and when added to water and stirred, it can be dispersed in water as fine particles.
[0039] Examples of polyisocyanates constituting the water-dispersible polyisocyanate include aliphatic isocyanates such as hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, tetramethylene diisocyanate, pentamethylene diisocyanate, lysine diisocyanate, and dimer acid diisocyanate; tolylene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, tetramethylxylylene diisocyanate, 1,5-naphthalene diisocyanate, 1,4-naphthalene diisocyanate, 4,4'-toluidine diisocyanate, 4,4'-diphenyl ether isocyanate, (m- or p-)phenylene diisocyanate, Examples of the polyisocyanate include aromatic polyisocyanates such as 4,4'-biphenylene diisocyanate, 3,3'-biphenylene diisocyanate, bis(4-isocyanatophenyl)sulfone, and isopropylidene bis(4-phenylisocyanate); and alicyclic diisocyanate compounds such as hydrogenated xylylene diisocyanate, isophorone diisocyanate, 4,4'-methylene bis(cyclohexyl isocyanate), methylcyclohexane-2,4-(or -2,6-) diisocyanate, 1,3-(or 1,4-)di(isocyanatomethyl)cyclohexane, 1,4-cyclohexane diisocyanate, 1,3-cyclopentane diisocyanate, and 1,2-cyclohexane diisocyanate. As such a polyisocyanate compound, a polyisocyanate compound having an isocyanurate structure, a urethane structure, a biuret structure, an allophanate structure, a uretdione structure, a trimer structure, etc. A so-called blocked isocyanate in which an isocyanate group is blocked with an active hydrogen group may also be used.
[0040] The matrix is preferably formed from one or a mixture of these polar polymers.
[0041] <Filler particles 2> The filler particles improve the elastic modulus. The shape of the filler particles may be spherical, such as a perfect sphere or an oblate spheroid, polyhedral, irregular, plate-like, scaly, needle-like, or fibrous. The length of the low aspect ratio needle-like or fibrous filler particles is, for example, 100 μm or less, preferably 30 μm or less, and more preferably 10 μm or less.
[0042] The length of the fibrous filler particles can be referred to as the fiber length. The length of the fibrous filler particles with a high aspect ratio may be 100 μm or more. The fiber length of the fibrous filler particles is less than 10 mm, may be 6 mm or less, may be 3 mm or less, or may be 1 mm or less. It is preferably 500 μm or less, more preferably 300 μm or less. The particle diameter of the fibrous filler particles can be referred to as the fiber diameter. The suitable range of the fiber diameter of the fibrous filler particles may be the same as the particle diameter of the filler particles. The fiber diameter of the fibrous filler particles is preferably 100 μm or less, more preferably 50 μm or less, and even more preferably 30 μm or less. The fiber diameter of the fibrous filler particles may be 10 μm or less, but is preferably 1 μm or more, and more preferably 3 μm or more. The aspect ratio of the fibrous filler particles is defined as the ratio of the fiber length to the fiber diameter (fiber length / fiber diameter). The aspect ratio of the fibrous filler particles is 3 or more, for example 5 or more, for example 1000 or less. The aspect ratio is more preferably 300 or less, and even more preferably 100 or less. The aspect ratio may be 10 or more, or less than 10, or 30 or more, or less than 30.
[0043] 2(a) and (b) show the morphology of the resin composition 10 of the embodiment when the filler particles 2 with a high aspect ratio are used. FIG. 2(c) shows the morphology of a comparative resin composition 30 when the filler particles 2 with a high aspect ratio are used. In the form of FIG. 2(a) and (b), the filler particles 2 have an independent dispersion structure separated from the elastomer particles 3 via the matrix 1. In the form of FIG. 2(c), the elastomer material 4 is attached to the filler particles 2 with a high aspect ratio and dispersed as one body, forming an attached dispersion structure. In the resin composition 30 having an attached dispersion structure, the filler particles 2 are in contact with the elastomer material 4 and are not separated. In the resin composition 10 of the embodiment, the filler particles 2 with a high aspect ratio as shown in FIG. 2(a) and (b) have an independent dispersion structure, so that excellent mechanical properties, such as bending modulus and impact strength, and excellent flame retardancy can be achieved at the same time. FIG. 2(b) shows a state in which additive particles 8 are dispersed in elastomer particles 3, which will be described later.
[0044] Filler particles mainly composed of inorganic materials are not particularly limited, but examples thereof include particles such as mica, glass fiber, glass spheres, zinc oxide, titanium oxide (titania), zirconium oxide (zirconia), hafnium oxide (hafnia), zinc titanate, magnesium titanate, strontium titanate, calcium titanate, calcium zirconate, calcium carbonate, clays, talc, silicon oxide (silica), wollastonite, forsterite, zeolite, diatomaceous earth, silica sand, fly ash, pumice powder, slate powder, aluminum oxide (alumina), alumina white, aluminum sulfate, carbon fiber, carbon nanotubes, metal fiber, barium sulfate, calcium sulfate, molybdenum disulfide, shirasu balloon, and fly ash balloon. The first filler particles 2a and the second filler particles 2b preferably contain silica or calcium carbonate. It is also preferable that the first filler particles 2a and the second filler particles 2b contain glass fiber or carbon fiber.
[0045] The filler particles may have a base made of an inorganic material that is the main component of the filler particles, and a surface layer made of an organic material or an inorganic material that covers the base. The thickness of the surface layer is, for example, 100 nm or less, and preferably 10 nm or less. In filler particles mainly made of an inorganic material, the volume occupied by the inorganic material is larger than the volume occupied by the organic material, and is preferably 90 volume % or more.
[0046] FIG. 3 is a schematic diagram for explaining the occurrence of cracks in a molded body obtained by molding the resin composition of this embodiment. As shown in FIG. 3, when an impact is applied to the resin molded body so that deformation occurs in the direction of the arrow 7, the matrix 1 is oriented around the elastomer particle 3, and crazes 5 are formed, so that the impact can be more efficiently alleviated. At this time, in order to avoid a decrease in impact strength due to the filler particle 2 becoming a material defect, it is preferable that the filler particle has a small particle diameter. As shown in FIG. 3(a), when the filler particle 2 is a coarse particle with a large particle diameter, the filler particle 2 acts as a stress concentration point, so that the impact strength decreases and the crack 6 may progress. On the other hand, in order to sufficiently disintegrate and disperse the particles in the resin composition production process, it is preferable to avoid poor dispersion due to particle aggregation caused by a small particle diameter. As shown in FIG. 3(b), when the filler particle 2 is a fine particle with a small particle diameter, it may be difficult to disperse the filler particles due to particle aggregation in the resin composition production process. As a result, material defects occur due to particle aggregation, which leads to a decrease in impact strength and the crack 6 may progress.
[0047] Therefore, the particle diameter of the filler particles 2 that are dispersed independently is, for example, 10 μm or less, preferably 5 μm or less, and preferably 2 μm or less. If the particle diameter of the filler particles 2 is 10 μm or less, the decrease in impact strength due to the addition of the filler particles 2 can be suppressed well. Furthermore, if the particle diameter is 0.2 μm or more, the filler particles 2 can be finely dispersed well in the matrix 1, and the decrease in impact strength can be suppressed. Therefore, the particle diameter of the filler particles 2 is preferably 0.2 μm or more and 10 μm or less, more preferably 0.2 μm or more and 5 μm or less, and even more preferably 0.2 μm or more and 2 μm or less. It is preferable that the filler particles having a particle diameter of 2 μm or more that can be contained in the multiple filler particles 2 are separated from the elastomer particles 3 that are present closest to the filler particles having a particle diameter of 2 μm or more via the matrix 1. Therefore, at least one of the first filler particles 2a and the second filler particles 2b described above may have a particle diameter of 2 μm or more. The resin composition 10 may contain filler particles 2 having a particle diameter exceeding 10 μm. The particle diameter of the filler particles 2 having a particle diameter exceeding 10 μm is preferably 100 μm or less, more preferably 50 μm or less, and even more preferably 30 μm or less.
[0048] When the filler particles 2 are fibrous or the like and have an aspect ratio of 5 or more (high aspect ratio), as shown in FIG. 3(c), the area of the interface between the matrix 1 and the filler particles 2 is large, so that the impact is mitigated while the crack 6 advances along the interface. For this reason, a large aspect ratio is preferable. For this reason, the aspect ratio of the independently dispersed filler particles 2 is preferably, for example, 5 or more. If the aspect ratio of the filler particles 2 is 5 or more, the decrease in impact strength due to the addition of the filler particles 2 can be suppressed well. The aspect ratio of the filler particles 2 is preferably 10 or more, and preferably 15 or more. On the other hand, in order to sufficiently disperse the filler particles 2 in the manufacturing process of the resin composition, it is preferable to avoid poor dispersion due to the aggregation of the filler particles 2 caused by a high aspect ratio. If the aspect ratio of the filler particles 2 is too high, the filler particles 2 may become difficult to disperse in the manufacturing process of the resin composition due to entanglement of the filler particles 2. As a result, material defects due to aggregation may occur, leading to a decrease in impact strength and the progression of cracks 6. If the aspect ratio of the filler particles 2 is 100 or less, the filler particles 2 can be well dispersed in the matrix 1, and a decrease in impact strength can be suppressed. The first filler particles 2a and the second filler particles 2b may have an aspect ratio of 5 or more and 100 or less.
[0049] The particle size can be measured by, for example, the following method. That is, a transverse cross-sectional sample of a molded product obtained by molding the resin composition of this embodiment is prepared by pretreatment such as cross-sectional polishing, microtome, and ion milling. Ion milling is preferable because it provides high smoothness of the cross section and suppresses particle dropout. If the temperature of the resin composition increases due to processing, cooling such as cryo-treatment may be performed. Thereafter, observation is performed using a scanning electron microscope (SEM) under the conditions shown below to obtain an SEM image of the cross section. It is preferable to use different observation magnifications depending on the particle size of the filler particles. For example, when the particle size is 5 μm or less, observation is performed at a magnification of 10,000 times, and when the particle size is more than 5 μm, observation is performed at a magnification of 1,000 times. From the obtained SEM image, the median diameter (50% particle diameter) of the filler particles in an arbitrary range of the cross section of the molded product is determined as the particle diameter of the filler particles by binarization and image analysis. Any range of the cross section of the molded body can be, for example, a quadrilateral region with the lengths of two adjacent sides being length L and length M. The length L and length M are, for example, 5 μm or more, preferably 10 μm or more, for example, 500 μm or less, for example, 100 μm or less. The length L and length M may be the same or different, and the ratio of the length L to the length M may be 0.5 to 2. Note that the binarization and image analysis of the SEM image can be performed using the image processing software ImageJ (available from https: / / imagej.nih.gov / ij / ) of the National Institutes of Health. The average diameter of the particles measured so as to pass through the center of gravity of the filler particles in the cross section of the molded body can be determined as the particle diameter of the filler particles.
[0050] The method for measuring the aspect ratio includes, for example, the following method. That is, the molded product obtained by molding the resin composition of this embodiment is subjected to a pyrolysis treatment or a dissolution treatment using a solvent to remove organic components, and only the filler particles are extracted to prepare an aspect ratio measurement sample. Then, observation is performed under the conditions shown below using a scanning electron microscope (SEM) to obtain a cross-sectional SEM image. It is preferable to use different observation magnifications depending on the length of the filler particles. For example, when the length is 5 μm or less, it is preferable to observe at a magnification of 10,000 times, and when the length is more than 5 μm, it is preferable to observe at a magnification of 1,000 times. Furthermore, when the length of the filler particles exceeds 100 μm, the filler particles are divided into multiple SEM images to obtain an SIM image of the entire filler particles. From the obtained SEM image, the average value of the aspect ratios in any range of the SEM image obtained by binarization and image analysis under the conditions shown below is taken as the aspect ratio of the filler particles. Any range of the cross section of the molded body can be, for example, a quadrilateral region in which the lengths of two adjacent sides are length L and length M. The length L and length M are, for example, 5 μm or more, preferably 10 μm or more, for example, 500 μm or less, for example, 100 μm or less. The length L and the length M may be the same or different, and the ratio of the length L to the length M may be 0.5 to 2. Note that the binarization and image analysis of the SEM image can be performed using the image processing software ImageJ (available from https: / / imagej.nih.gov / ij / ) of the National Institutes of Health. The maximum diameter of the filler particle measured so as to pass through the center of gravity of the filler particle in the cross section of the molded body is the filler particle length, the diameter measured from the center of gravity in a direction perpendicular to the maximum diameter is the filler particle diameter, and the filler particle length ÷ filler particle diameter is the aspect ratio of each filler particle, and the average value can be calculated.
[0051] The filler particles are preferably surface-treated with a surface treatment agent such as a coupling agent or a fatty acid. For the surface-treated filler particles, a commercially available product that has been surface-treated in advance may be used, or a separate surface treatment step may be provided during the production of the resin composition. The amount of the surface treatment agent used can be calculated from the specific surface area of the filler particles to be treated and the minimum coverage area of the surface treatment agent. When using filler particles with a small particle size, the specific surface area of the filler particles increases, so the amount of the surface treatment agent used inevitably increases. For this reason, there is a range of amounts of the surface treatment agent used, and it is common to add about 0.5 wt% to 5 wt% to the filler particles. The treatment method can be a known method such as a dry treatment method such as an integral blend method or a wet treatment method using an aqueous solution of the surface treatment agent. The surface layer formed by the surface treatment constitutes a part of the filler particles.
[0052] Examples of the surface treatment agent include silane coupling agents such as vinyltrimethoxysilane, vinyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, tris-(trimethoxysilylpropyl)isocyanurate, and 3-trimethoxysilylpropylsuccinic anhydride. Titanate-based and aluminate-based coupling agents may also be used. Examples of fatty acids include lauric acid, stearic acid, and oleic acid. Among these, silane coupling agents are preferred. These surface treatment agents may be used alone or in combination of two or more.
[0053] <Elastomer particles 3, elastomer material> The elastomer material constituting the elastomer particles 3 improves impact strength. The elastomer material is a copolymer consisting of a combination of hard segments that act as crosslinking points and soft segments that exhibit rubber elasticity, and is preferably a thermoplastic elastomer that has both the properties of plastic and rubber.
[0054] Examples of the elastomer material include urethane-based elastomers, ester-based elastomers, amide-based elastomers, acrylic-based elastomers, olefin-based elastomers, styrene-based elastomers, etc. The elastomer material is preferably an acrylic-based elastomer or an ester-based elastomer.
[0055] Examples of urethane-based elastomers include elastomers in which the hard segment is polyurethane containing a urethane group and the soft segment is polyester containing an ester bond or polyether containing an ether bond. Note that the urethane group and the ester bond have polarity.
[0056] Examples of the ester-based elastomer include elastomers in which the hard segment is a polyester containing an ester bond and the soft segment is a polyester containing an ester bond or a polyether containing an ether bond. Note that the ester bond has polarity.
[0057] Examples of amide-based elastomers include elastomers in which the hard segment is a polyamide containing an amide group and the soft segment is a polyester containing an ester bond or a polyether containing an ether bond. Note that the amide group and the ester bond have polarity.
[0058] Examples of acrylic elastomers include elastomers in which the hard segment is polymethyl methacrylate, which is a polymer of methyl methacrylate and has an ester bond, and the soft segment is a copolymer of butyl acrylate, 2-ethylhexyl acrylate, or the like, which has an ester bond. Also included are elastomers in which the hard segment is a polyolefin such as polyethylene, and the soft segment is polymethyl methacrylate, which is a polymer of methyl methacrylate and has an ester bond. Note that the ester bond has polarity.
[0059] Examples of olefin-based elastomers include elastomers in which the hard segment is a polyolefin such as polypropylene or polyethylene, and the soft segment is an ethylene propylene rubber or an ethylene propylene diene rubber.
[0060] Examples of styrene-based elastomers include elastomers in which the hard segment is polystyrene and the soft segment is butadiene, isoprene, ethylene, or the like.
[0061] From the viewpoint of affinity with the matrix, which is a polar polymer, the elastomer material preferably has a polar group. Examples of the polar group that the elastomer material has include a urethane group, an amide group, and an ester bond. In particular, the elastomer material preferably has an ester bond in either or both of the hard segment and the soft segment.
[0062] The elastomer material has a polar group such as an ester bond, and thus the elastomer material has heat resistance and can be melt-kneaded with a polar polymer, particularly a polar polymer with high heat resistance. In addition, the elastomer material having an ester bond has relatively high mechanical properties, which contributes to the improvement of physical properties, which is the object of the present invention.
[0063] The glass transition point (glass transition temperature) of the elastomer material is lower than room temperature, so that the elastomer acts as an elastomer at room temperature. The glass transition point of the elastomer material is preferably lower than 0°C, and more preferably -20°C or lower.
[0064] The impact strength is improved by melt-kneading the elastomer material with the matrix, which is a thermoplastic resin, in a molten state and finely dispersing it in the matrix 1 as elastomer particles 3. Therefore, in order to be able to melt-knead with the matrix, it is preferable that the melting point of the elastomer material is lower than the heating temperature (molding temperature) of the resin composition. The heating temperature of the resin composition is the temperature at which the matrix, which is a thermoplastic polymer, melts, and is higher than the glass transition point of the matrix, and if the matrix is a crystalline polymer, it is preferable that it is higher than the melting point of the matrix. Therefore, it is preferable that the melting point of the elastomer material is lower than the melting point of the matrix. The melting point of the elastomer material may be higher than the melting point of the matrix, but this may cause thermal degradation, such as a decrease in the molecular weight of the matrix due to heating the matrix to melt the elastomer material. When the matrix is a crystalline polymer, the melting point of the elastomer material may be higher than the glass transition point of the matrix. When the matrix is an amorphous polymer, the melting point of the matrix is not defined, so it is preferable that the melting point of the elastomer material is lower than the glass transition point of the matrix.
[0065] The glass transition point of the matrix is preferably 50° C. or higher to ensure strength during use, and also preferably 200° C. or lower in consideration of processability. The melting point of the matrix is preferably 100° C. or higher, and preferably 200° C. or higher in consideration of heat resistance, and preferably 300° C. or lower in consideration of processability. The melting point of the elastomer material is preferably 50° C. or higher to ensure strength during use, and preferably 300° C. or lower, and preferably 200° C. or lower in consideration of processability.
[0066] The elastomer material contributes to improving the impact strength of the matrix because of its rubber elasticity, i.e., flexibility. As shown in FIG. 3, when an impact is applied to a molded body obtained by molding the resin composition of this embodiment, the matrix 1 is oriented around the elastomer particles 3, and crazes 5 are formed, so that the impact can be more efficiently alleviated. On the other hand, because of its flexibility, the elastic modulus of the resin composition may decrease depending on the amount of the elastomer material added. For this reason, in order to simultaneously improve the impact strength and elastic modulus of the matrix, it is preferable to use an elastomer material with high hardness. Regarding the rubber hardness of the elastomer material, the Shore A hardness is preferably 70 degrees or more, more preferably 80 degrees or more, and even more preferably 90 degrees or more.
[0067] As described above, it is preferable that a large number of elastomer particles 3 are finely dispersed because the crazes 5 generated around the elastomer particles 3 absorb impact energy and impact strength. For this reason, the particle size of the elastomer particles 3 is preferably 10 μm or less, more preferably 5 μm or less. In order for the elastomer particles 3 to function efficiently mechanically, the particle size of the elastomer particles 3 is preferably 0.1 μm or more, more preferably 0.5 μm or more. The elastomer particles 3 are typically particles formed by dispersing and mixing by melt kneading, which will be described later, and the particle size of such elastomer particles 3 can be referred to as the dispersed particle size or dispersed particle size.
[0068] The particle diameter of the elastomer particles 3 dispersed in the matrix 1 can be calculated from the cross-section observation of the resin molded body in the same manner as the measurement method of the particle diameter of the filler particles 2. Specifically, a transverse cross-section sample of the molded body is produced in the same manner as the measurement method of the particle diameter of the filler particles 2. Thereafter, an SEM observation is performed under the same conditions as the measurement method of the particle diameter of the filler particles 2 to obtain an SEM image of the cross section. In the same manner as the measurement method of the particle diameter of the filler particles 2, the median diameter of the elastomer particles 3 in an arbitrary area range of the molded body cross section is determined as the particle diameter of the elastomer particles 3 from the SEM image by binarization and image analysis. The arbitrary area range of the molded body cross section can be, for example, a quadrilateral region whose two adjacent sides have lengths L and M. The length L and length M are, for example, 5 μm or more, preferably 10 μm or more, and, for example, 500 μm or less, for example, 100 μm or less. The length L and the length M may be the same or different, and the ratio of the length L to the length M may be 0.5-2.
[0069] <Composition ratio of each component> The matrix 1 acts as a matrix that disperses the filler particles 2 and the elastomer particles 3 independently. The resin composition 10 of the present embodiment can obtain mechanical properties superior to those of the matrix 1 by independently dispersing the filler particles 2 and the elastomer particles 3. Therefore, the content of the matrix 1 is, for example, 30% by mass or more, preferably 40% by mass or more, and more preferably 50% by mass or more, based on the total amount of the resin composition. The content of the matrix 1 is, for example, 90% by mass or less, preferably 80% by mass or less, and more preferably 70% by mass or less, based on the total amount of the resin composition. The composition ratio in the resin composition can be obtained by performing thermogravimetric analysis (TGA).
[0070] The composition ratio of the filler particles 2 and the elastomer material can be appropriately adjusted within a range that does not deviate from the preferred composition ratio range of the matrix 1 according to the required mechanical property values. When the filler particles 2 are present in a large amount, the elastic modulus can be increased, and when the elastomer material is present in a large amount, the impact strength can be increased. For this reason, the content of the filler particles 2 is, for example, 1% by mass or more, preferably 5% by mass or more, and preferably 10% by mass or more, relative to the total amount of the composition. The content of the filler particles 2 is, for example, 50% by mass or less, preferably 40% by mass or less, and more preferably 30% by mass or less, relative to the total amount of the composition. The content of the elastomer material is, for example, 1% by mass or more, preferably 5% by mass or more, and preferably 10% by mass or more, relative to the total amount of the composition. The content of the elastomer material is, for example, 50% by mass or less, preferably 40% by mass or less, and preferably 30% by mass or less, relative to the total amount of the composition. The content of the matrix 1 is preferably greater than the content of the filler particles 2 and the content of the elastomer material. The content of the filler particles 2 is, for example, 1 / 5 or more and 5 or less, or 1 / 4 or more and 4 or less, the content of the elastomer material. The content of the filler particles 2 can be 1 or more times the content of the elastomer material.
[0071] In the resin composition 10 of this embodiment, it is preferable that a structure in which the filler particles 2 and the elastomer particles 3 are independently dispersed in the matrix 1 is ubiquitous over a wide volume range of the entire resin composition 10. In such a case, the composition ratio of the matrix, the filler particles, and the elastomer material in the entire resin composition 10 and the ratio of the filler particles to the elastomer material in the entire resin composition 10 are 100% or less. 3 μm 3 More than 1mm 3 The compositions in the following moderately wide volume ranges are generally consistent. 3 μm 3 More than 1mm 3 The composition in the following volume range can be approximated by the composition ratio to the total amount of the resin composition described above. 3If it can be confirmed that the independent dispersed structures are ubiquitous over a wide volume range exceeding 1 mm 3 A wide range of volumes (e.g. 10 to 100 mm 3 Thermogravimetric analysis (TGA) can be performed on the resin composition 10 in the volume range of 100 3 μm 3 More than 1mm 3 The composition may be in the following volume ranges:
[0072] In addition, 100 3 μm 3 More than 1mm 3 The volume ratios in the following moderately broad volume ranges vary depending on the density of each component, but the following ranges are preferred: the volume ratio of the matrix 1 is, for example, 35 volume % or more and, for example, 92 volume % or less; the volume ratio of the filler particles 2 is, for example, 2 volume % or more and, for example, 33 volume % or less; and the volume ratio of the elastomer material is, for example, 7 volume % or more and, for example, 58 volume % or less.
[0073] <ΔHSP value> The affinity between two components is correlated with the solubility parameter. Specifically, the affinity between two components can be controlled by the difference in HSP values (ΔHSP value) between the two components, which is calculated from the Hansen solubility parameters (HSP value). When the ΔHSP value between two components is small, the affinity between the two is high and they tend to be attracted to each other. On the other hand, when the ΔHSP value between two components is large, the affinity between the two is low and they tend to be independent.
[0074] The HSP value is the energy due to the dispersion force between molecules, δd (MPa 1 / 2 ), and the energy due to intermolecular dipole interactions δp (MPa 1 / 2 ), and the energy due to hydrogen bonds between molecules δh (MPa 1 / 2 ) and the HSP value is obtained as the vector sum of these three energies. The vector difference of the HSP value between two components is called ΔHSP and can be calculated using the following formula (1).
[0075] ΔHSP value = {4(δdA-δdB) 2 +(δpA-δpB) 2 +(δhA-δhB) 2} 1 / 2 (1) HSP values of many substances have been calculated by Hansen and his successors, and are described in Polymer Handbook (fourth edition), VII-698-711, and Industrial Solvents Handbook by Wesley L. Archer. HSP values can also be calculated using software such as Hansen Solubility Parameter in Practice (HSPiP, Charles M. Hansen URL: http: / / www.hansen-solubility.com / ).
[0076] The ΔHSP value described in this embodiment was calculated using the database-attached calculation software "HSPiP" 5th Edition 5.4.01 developed and sold by the Hansen Group, by inputting the chemical structural formula of the compound.
[0077] In order to disperse the filler particles and elastomer particles independently in the matrix, it is preferable to control the affinity between the surface of the filler particles and the elastomer material. If the ΔHSP value of the two is small, they tend to be attracted to each other and form a core-shell structure as shown in Figure 1(b). On the other hand, if the ΔHSP value of the two is large, they tend to be independent in the matrix and form an independent particle dispersion structure as shown in Figure 1(a), which makes it possible to obtain excellent mechanical properties.
[0078] When the inventors calculated the ΔHSP value of the surface of the filler particles and the elastomer material, they found that the affinity differs depending on the combination. In other words, by appropriately selecting the combination of the surface of the filler particles (or the surface treatment agent if the filler particles are surface-treated) and the elastomer material, the elastomer material is dispersed in a particulate form in the matrix. This makes it possible to form an independent particle dispersion structure of the filler particles and the elastomer particles in the matrix, and to obtain excellent mechanical properties.
[0079] To form an independent particle dispersion structure, the ΔHSP value of the surface of the filler particles and the elastomer material is, for example, 6.5 MPa. 1 / 2 Larger than 7.0MPa 1 / 2 More preferably, 7.6MPa or more. 1 / 2 It is more preferable that the ΔHSP value of the surface of the filler particle and the elastomer material is 15.0 MPa or more. 1 / 2 It may be less than 10.0MPa 1 / 2 The ΔHSP value of the matrix and the elastomer material may be, for example, 6.0 MPa or less. 1 / 2 Larger, 6.7MPa 1 / 2 It is preferable that the pressure is 7.0MPa or more. 1 / 2 More preferably, the ΔHSP value of the matrix and the elastomer material is 15.0 MPa or more. 1 / 2 It may be less than 10.0MPa 1 / 2 The ΔHSP value of the matrix and the surface of the filler particles may be, for example, 7.0 MPa or less. 1 / 2 Above 9.0MPa 1 / 2 It is preferable that the temperature is 11.0MPa or more. 1 / 2 It is more preferable that the ΔHSP value of the matrix and the surface of the filler particle is 20.0 MPa or more. 1 / 2 It may be less than 15.0MPa 1 / 2 It may be the following.
[0080] <Other ingredients> The resin composition of the present embodiment may contain various other additives as necessary. The type of additive is not particularly limited as long as it is one that is generally used in compounding thermoplastic resins and thermoplastic elastomer materials. Examples of various additives that improve functionality include flame retardants, waxes, lubricants and release agents such as various fatty acids, fatty acid amides, fatty acid esters, and metal salts of fatty acids, various antistatic agents, fatty acid esters, sliding properties improvers such as polyolefins and olefin copolymer elastomers, and polysiloxanes, decomposition inhibitors such as polyamide resins and acrylamide polymers, amide compounds, amino-substituted triazine compounds and derivatives thereof, urea and derivatives thereof, hydrazine derivatives, imidazole compounds, imide compounds, and epoxy compounds, formic acid scavengers such as melamine and hydroxides and carbonates of alkali metals, and flame retardants such as organic phosphorus compounds. Examples of various additives that improve long-term stability include ultraviolet absorbers such as benzotriazole compounds, benzophenone compounds, and phenyl salicylate compounds, hindered amine light stabilizers, and hindered phenol antioxidants. The above additives may be used in combination of one or more kinds.
[0081] The resin composition of the present embodiment may contain at least one of a metal material containing a transition metal element, a compound material containing a transition metal element, a metal material containing a typical metal element, and a compound material containing a typical metal element, which are different from the inorganic material that is the main component of the above-mentioned first filler particles 2a.
[0082] Examples of transition metal elements include titanium (Ti), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zirconium (Zr), niobium (Nb), molybdenum (Mo), hafnium (Hf), tantalum (Ta), tungsten (W), palladium (Pd), platinum (Pt), silver (Ag), gold (Au), etc. Examples of typical metal elements include sodium (Na), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), zinc (Zn), aluminum (Al), gallium (Ga), germanium (Ge), indium (In), tin (Sn), antimony (Sb), etc. Silicon (Si) and arsenic (As) can be classified as semimetals together with germanium (Ge) and antimony (Sb), but here, silicon (Si) and arsenic (As) are treated as nonmetallic elements. The metal material is a metal element or an alloy, and the metal compound, which is a compound containing a metal element, is, for example, an oxide, nitride, carbide, inorganic acid salt, or organic acid salt of a metal element. The metal compound may be a composite compound containing multiple transition metal elements, multiple typical metal elements, or a transition metal element and a typical metal element. Compounds are classified into inorganic compounds and organic compounds, and an organic compound, which is a metal compound, that is, an organometallic compound, is a compound having a bond between carbon and a metal element. Among these, the inorganic compound can also be used as the inorganic material that is the main component of the first filler particle 2a. Titanium oxide (titania), zirconium oxide (zirconia), hafnium oxide (hafnia), zinc titanate, magnesium titanate, strontium titanate, calcium titanate, calcium zirconate, etc., which are also listed as inorganic materials as the main component of the filler particles, contain transition metal elements, and some of these are composite compounds containing transition metal elements and typical metal elements. Many transition metal compounds have a high dielectric constant (relative dielectric constant of 10 or more). By containing such a high dielectric constant material in the resin composition, the dielectric constant of the resin composition 10 containing the matrix 1, which typically has a low dielectric constant (relative dielectric constant less than 10), can be increased, and the radio wave shielding property can be improved by utilizing the dielectric loss.Even when the resin composition 10 contains a metal material, the radio wave shielding properties can be improved due to the electrical conductivity of the metal material.
[0083] The material containing the transition metal element or typical metal element listed here may be the main component of the second filler particles 2b, but it is preferable that the inorganic material that is the main component of the first filler particles 2a and the inorganic material that is the main component of the second filler particles 2b are the same.
[0084] The materials containing a transition metal element or a typical metal element listed here may be filler particles (part of the plurality of filler particles 2) having a particle diameter of 0.1 μm or more dispersed in the matrix 1, or may be particles having a particle diameter of less than 0.1 μm. The materials containing a transition metal element or a typical metal element listed here may be particles smaller than the elastomer particles 3, or may be particles dispersed in the elastomer particles 3. Alternatively, the materials containing a transition metal element or a typical metal element listed here may be dissolved in the matrix 1 or the elastomer particles 3.
[0085] FIG. 2(b) shows a form in which additive particles 8 are dispersed in elastomer particles 3. The additive particles 8 and elastomer particles 3 have a core-shell structure with the additive particles 8 as the core and the elastomer particles 3 as the shell. As long as there are a plurality of filler particles 2 independently dispersed in a plurality of elastomer particles 3, the additive particles 8 do not have to be independently dispersed in the elastomer particles 3. The additive particles 8 may be attached to and in contact with the elastomer particles 3. The additive particles 8 may also be attached to and in contact with the filler particles 2. The additive particles 8 attached to the elastomer particles 3 may or may not be in contact with the matrix 1.
[0086] The content of the material containing the transition metal element or typical metal element listed here is preferably less than the content of the polar polymer that is the main component of the matrix 1, the inorganic material that is the main component of the first filler particles 2a, and the elastomer material that is the main component of the elastomer particles 3.
[0087] When the content of a specific metal element is different between the matrix 1 and the elastomer material, the matrix 1 and the elastomer material in the observation image can be easily distinguished by acquiring a distribution image (mapping image) of the metal element. For example, aluminum (Al), germanium (Ge), antimony (Sb) or titanium (Ti) can be contained in a compound as a polymerization catalyst when polymerizing a polar polymer, and can be dissolved or dispersed in the matrix 1. Alternatively, a material containing a transition metal element or a typical metal element can be contained in a compound as a pigment for coloring a resin composition, and can be dispersed in the matrix 1. Alternatively, the multiple filler particles 2 can include, for example, filler particles mainly composed of calcium carbonate and filler particles mainly composed of titanium oxide, and both of these can be dispersed independently.
[0088] The additive may include a bromine compound, a phosphorus compound, a chlorine compound, an antimony compound, a nitrogen compound, a boron compound, etc. These compounds may be used as flame retardants. For example, many organic acid salts containing phosphorus are flame retardants such as aluminum phosphates, aluminum phosphinates, and derivatives thereof. The flame retardancy of the resin composition can be improved by including such a flame retardant in the resin composition. If the flame retardant is dispersed or dissolved in the elastomer particles 3, the flame retardancy can be improved efficiently. This is because the elastomer particles 3 are easily combustible. The additive particles 8 dispersed in the filler particles 3 shown in FIG. 2(b) may be the flame retardant.
[0089] <Proportion of Independently Dispersed Filler Particles 2> The ratio of the independently dispersed filler particles 2 can be calculated from the cross-sectional observation of the resin molded body. 2 μm 2From the above area range, A filler particles 2 are extracted. The number of filler particles 2 extracted (A) may be 10 or more, and may be 100 or less. Among the A extracted filler particles 2, the number of filler particles 2 that are separated from the nearest elastomer particle 3 via a matrix 1 (B) is counted. The proportion of independently dispersed filler particles can be calculated from the ratio of the number of particles (B) to the number of extracted filler particles 2 (A).
[0090] Specifically, a cross-sectional sample of the molded product is prepared in the same manner as in the measurement method of the particle diameter of the filler particles 2. Then, observation is performed by SEM under the same conditions as in the measurement method of the particle diameter of the filler particles 2 to obtain an SEM image of the cross section. From the obtained SEM image, A (10 or more) filler particles 2 are counted by binarization and image analysis in the same manner as in the measurement method of the particle diameter of the filler particles 2, and among them, the number (B) of filler particles 2 separated from the nearest elastomer particle 3 is counted. Then, the presence ratio of independently dispersed filler particles 2 is calculated using the following formula (2).
[0091] Proportion of independently dispersed filler particles 2 X (number%) = (B / A) × 100 (quantity%) (2) X (% by number) is, for example, a majority of 50% by number or more, preferably 70% by number or more, more preferably 80% by number or more, and even more preferably 90% by number or more.
[0092] <Proportion of independently dispersed elastomer particles 3> The proportion of the independently dispersed elastomer particles 3 can be calculated from the cross-sectional observation of the resin molded product. 2 μm 2From the above area range, C elastomer particles 3 are extracted. The number of extracted elastomer particles 3 (C) may be 10 or more, but may be 100 or less. Among the extracted C elastomer particles 3, the number (D) of elastomer particles 3 that are separated from the nearest filler particle 2 via a matrix 1 is counted. The proportion of independently dispersed elastomer particles 3 can be calculated from the ratio of the number (D) of particles to the number (C) of extracted elastomer particles 3.
[0093] Specifically, a cross-sectional sample of the molded product is prepared in the same manner as in the measurement of the particle size of the elastomer particles 3. Then, observation is performed by SEM under the same conditions as in the measurement of the particle size of the elastomer particles 3 to obtain an SEM image of the cross section. From the obtained SEM image, C (10 or more) elastomer particles 3 are counted by binarization and image analysis in the same manner as in the measurement of the particle size of the elastomer particles 3, and among them, the number (D) of elastomer particles 3 separated from the filler particles 2 is counted. Then, the presence ratio of independently dispersed elastomer particles 3 is calculated using the following formula (3).
[0094] Proportion Y of independently dispersed elastomer particles 3 (number%) = (D / C) × 100 (quantity%) (3) Y (% by number) is, for example, a majority of 50% by number or more, preferably 70% by number or more, more preferably 80% by number or more, and even more preferably 90% by number or more.
[0095] <Area occupancy rate> 10 of the observed cross section of the resin composition 10 2 μm 2In the above area range, the matrix 1 occupies, for example, 30 area% or more, for example, 90 area% or less, and preferably 70 area% or less. In this area range, the elastomer material occupies, for example, 1 area% or more, preferably 5 area% or more, for example, 50 mass% or less, and preferably 30 area% or less. In this area range, the filler particles 2 occupy, for example, 1 area% or more, preferably 5 area% or more, for example, 50 mass% or less, and preferably 30 area% or less. This area range preferably includes the above-mentioned first elastomer particles 3a, second elastomer particles 3b, first filler particles 2a, and second filler particles 2b.
[0096] 10 of the observed cross section of the resin composition 10 2 μm 2 The occupancy rate of each material in the above area range can be calculated from a cross-sectional observation of a molded product of the resin composition 10. Specifically, a transverse cross-sectional sample of the molded product is produced in the same manner as in the measurement method of the particle diameter of the filler particles 2. Then, an SEM observation is performed under the same conditions as in the measurement method of the particle diameter of the filler particles 2 to obtain an SEM image of the cross section. In the SEM image taken with a scanning electron microscope, the filler particles 2, the matrix 1, and the elastomer material can be identified by the shape, size, and contrast in the obtained image. It is desirable to distinguish the filler particles 2, the matrix 1, and the elastomer material by mapping the elements contained in each material. Energy dispersive X-ray spectroscopy (EDS) can be used for element mapping. SEM-EDS, which combines the above-mentioned SEM and element analysis, is preferable. In addition, the obtained image is analyzed by a small general-purpose image processing and analysis system (LUZEX; Nicole Co., Ltd.). The obtained image is binarized at a predetermined threshold value, and the area ratio in the processed image is used to determine the area ratio of 10. 2 μm 2 The occupancy rate of each material in the above area range is calculated. The area range of the observed cross section of the resin composition 10 is, for example, 1000 2 μm 2 Less than or equal to 500 2 μm 2It is preferable that the value is equal to or less than 250. 2 μm 2 More preferably, it is 130 2 μm 2 It is even more preferable that:
[0097] <Method for producing resin composition> The method for producing the resin composition of the present embodiment includes a step of melt-kneading a matrix, filler particles, and an elastomer raw material containing an elastomer material constituting the elastomer particles. Examples of kneading devices include a twin-screw extruder and a twin-roller, and specific examples thereof include a TEM extruder (manufactured by Toshiba Machine Co., Ltd.), a TEX twin-screw kneader (manufactured by The Japan Steel Works, Ltd.), a PCM kneader (manufactured by Ikegai Iron Works Co., Ltd.), and a Kneadex (manufactured by Nippon Coke Co., Ltd.).
[0098] <Molded body> The molded article of this embodiment is obtained by molding the resin composition of this embodiment. Typical molding methods include extrusion molding from a mold and injection molding into a mold. Injection molding may be performed using pellets produced by extrusion molding from a mold. The resin composition molded by injection molding may be called an injection molded article. In addition, the molded article formed by injection molding may be further processed by blow molding or the like.
[0099] The Charpy impact value of the compact is 3kJ / m 2 More than 6 kJ / m is preferable. 2 More than 3 kJ / m is more preferable. 2 If it is less than this, there is a risk of cracks occurring during a drop test or the like.
[0100] The flexural modulus of the molded body is preferably 2300 MPa or more, more preferably 2600 MPa or more. When the flexural modulus is in this range, the deformation due to the expected external force is in the elastic deformation region, and the shape does not deform. On the other hand, when the flexural modulus is less than 2300 MPa, there is a possibility that the expected external force may cause plastic deformation, and therefore, there is a possibility that a thicker wall than before is required.
[0101] ≪Equipment≫ As shown in FIG. 4, the device 100 of this embodiment has members 10a and 10b formed by molding the resin composition 10 of this embodiment. Examples of the device 100 include office equipment such as printers and copiers, medical equipment such as CT, and imaging equipment such as projectors and displays. These various devices have at least one of an electric part 13, an optical part 12, and a metal part 11 in addition to the members 10a and 10b formed by molding the resin composition 10 of this embodiment. The electric part 13, the optical part 12, or the metal part 11 realizes the function of the device 100. The metal part 11 can also be used for a housing for ensuring the mechanical strength of the device 100.
[0102] The members 10a and 10b formed from the resin composition 10 can be used as members for ensuring the mechanical strength of the device 100 and for mechanically protecting the device 100. The member 10a formed from the resin composition 10 may be an exterior body of the device 100, for example, an exterior cover. This exterior body may be fixed to a metal housing (metal part 11). The member 10a formed from the resin composition 10 of this embodiment may be an interior body of the device 100, for example, a mechanical part. This interior body may be fixed to a metal housing (metal part 11). It is preferable that the members 10a and 10b formed from the resin composition 10 have radio wave shielding properties in terms of stable operation of the device 100 and suppression of radio wave radiation from the device 100. EXAMPLES
[0103] Examples 1 to 15 and Comparative Examples 1 to 3 The materials used in the present examples (including comparative examples) are as follows.
[0104] (A) Matrix material
[0105] [Table 1]
[0106] (B) Filler particles The average particle size [μm] of the filler particles shown in Table 2 is the catalog value of the product.
[0107] [Table 2]
[0108] (C) Surface treatment agent
[0109] [Table 3]
[0110] (D) Elastomer materials
[0111] [Table 4]
[0112] <Production of pellets of resin composition> The matrix materials shown in Tables 5 and 6 were dried in advance so that the moisture content was 100 ppm. This was to suppress hydrolysis during kneading, and the temperature and time conditions differ depending on the type of resin. The moisture content was measured using a polymer moisture meter "Aquatrac V (product name) manufactured by ITS Japan Co., Ltd."
[0113] Next, the filler particles are surface-treated as shown in Tables 5 and 6. The filler particles are placed in a mixer "SMV-20Ba (product name) manufactured by Kawata Corporation," and the surface treatment agent shown in Tables 5 and 6 is dripped in from above while stirring. The amount of surface treatment agent to be added is calculated using the following model formula (4) from the specific surface area of the filler particles (B) and the minimum coverage area of the surface treatment agent. The minimum coverage area was calculated by referring to the manufacturer's catalog and literature values. Amount of surface treatment agent added (g) = Mass of filler particles (g) × Specific surface area of filler particles (m 2 / g) / minimum coverage area of surface treatment agent (g) (4)
[0114] Thereafter, a raw material blend was prepared by adding the matrix material, filler particles, and elastomer material so that the mass percentage of each component in the final resin composition was the amount shown in Tables 5 and 6. When the filler particles were surface-treated, the mass percentage of the filler particles included the surface treatment agent.
[0115] In Examples 1 to 10 and Comparative Examples 1 to 3, the matrix material A-1, the filler particles B-1 to B-6, and the elastomer materials D-1 to D-10 were each fed by a weight feeder at a predetermined mass ratio. Prior to this feeding, the filler particles B-1 to B-6 were treated with the surface treatment agents C-1 to C-2 by the above-mentioned surface treatment method.
[0116] In Examples 11 to 15, matrix materials A-2 to A-3, filler particles B-2 to B-6, and elastomer materials D-1 to D-3 and D-6 were fed by weight feeders at a predetermined mass ratio, respectively. Prior to this feeding, the filler particles B-2 to B-6 were treated with surface treatment agents C-2 to C-3 by the above-mentioned surface treatment method.
[0117] The blend was melt-kneaded in a twin-screw extruder (product name: PCM30 manufactured by Ikegai Corporation) at a cylinder temperature of 260°C and a screw rotation speed of 250 rpm to produce strands, which were then cut and processed using a pelletizer to obtain pellets of the resin composition.
[0118] <Molding of resin molded products> The pellets of the obtained resin composition were dried in advance so that the moisture content was 100 ppm. The moisture content was measured in the same manner as the moisture content of the matrix material. Then, the pellets were injection molded using an injection molding machine "SE-180D (product name) manufactured by Sumitomo Heavy Industries, Ltd." at a cylinder temperature of 280°C and a mold temperature of 30°C to mold a rectangular test piece type B1 (length 80 mm x width 10 mm x thickness 4 mm) as specified in JIS K7152-1.
[0119] <Charpy impact value> The molded rectangular test piece was notched (shape A) using a notch processing machine "No. 189-PN (product name) manufactured by Yasuda Seiki Seisakusho Co., Ltd." in accordance with JIS K7111, and a notch (shape A) was made in the center with a depth of 2 mm, a notch tip radius of 0.25 mm, and a 45° notch. The test piece was destroyed from the back of the notch of the test piece using a Charpy impact tester "No. 258 (product name) manufactured by Yasuda Seiki Seisakusho Co., Ltd." in accordance with JIS K7111-1 with an energy of 1 J. The energy required for destruction was calculated from the angle at which the hammer, which had been swung up to 150°, swung up after the test piece was destroyed, and the average value of the measurements for the five test pieces was taken as the Charpy impact value.
[0120] The results of the Charpy impact tests were evaluated according to the following indices. The results are shown in Tables 5 and 6. The higher the Charpy impact strength, the better the evaluation. A: Charpy impact strength is 6kJ / m 2 The end. B: Charpy impact strength is 3kJ / m 2 More than 6kJ / m 2 less than. C: Charpy impact strength is 3kJ / m 2 less than.
[0121] <Flexural modulus> The molded rectangular test pieces were subjected to measurements in accordance with JIS K7171 using a three-point bending jig attached to a universal material testing machine "Instron 5581 (product name)" with a support distance of 64 mm and an indenter descending speed of 2 mm / min, and the bending modulus was calculated from the stress gradient in the specified strain range (0.05% to 0.25%). The average value of the measurements for five test pieces was taken as the bending modulus.
[0122] The flexural modulus was evaluated according to the following criteria, and the results are shown in Table 5. The higher the flexural modulus, the better the evaluation. A: Flexural modulus is 2,600 MPa or more. B: Flexural modulus is 2,300 MPa or more and less than 2,600 MPa. C: Flexural modulus is less than 2,300 MPa.
[0123] <ΔHSP value> The ΔHSP value was calculated by inputting the chemical structural formula of the compound using the 5th Edition 5.4.01 of "HSPiP," a calculation software with database developed and sold by the Hansen Group. The ΔHSP value of the filler particle surface and elastomer material is "ΔHSP value 1," the ΔHSP value of the matrix material and elastomer material is "ΔHSP value 2," and the ΔHSP value of the matrix material and filler particle surface is "ΔHSP value 3," as shown in Tables 5 and 6.
[0124] <Confirmation of dispersion structure> The center of the molded rectangular test piece was observed in the cross-sectional direction to confirm the dispersion structure of the filler particles and elastomer particles in the matrix. The cross-section to be observed was prepared by polishing using abrasive paper with grain sizes from #400 to #2500 in order, and then buffing using diamond slurry with a particle size of 0.5 μm. The dispersion structure was observed at a magnification of 10,000 times using a scanning electron microscope (JEOL Ltd., JSM-F100 (product name)) with an accelerating voltage of 3 kV.
[0125] As a result of the observation, the state shown in Fig. 1(a) is "independent dispersion", and the state shown in Fig. 1(b) is "core-shell", as shown in Tables 5 and 6. Also, a cross-sectional SEM image of Example 1 is shown in Fig. 5(a), and a cross-sectional SEM image of Comparative Example 1 is shown in Fig. 5(b). A cross-sectional SEM image of Example 3 is shown in Fig. 6.
[0126] <Proportion of Independently Dispersed Filler Particles> A cross section to be observed was prepared in the same manner as for confirming the dispersion structure. Then, observation was performed using a scanning electron microscope (SEM) under the conditions shown below to obtain an SEM image of the cross section. The observation magnification was changed according to the particle diameter of the filler particles. When the particle diameter was 5 μm or less, observation was performed at a magnification of 10,000 times, and when the particle diameter was more than 5 μm, observation was performed at a magnification of 1,000 times. The field of view area of the SEM image was 10 2 μm 2 More than or equal to 130 2 μm 2The total number of filler particles (A) (10 or more) was counted from the obtained SEM image by binarization and image analysis under the following conditions, and among them, the number of filler particles (B) that existed separated from the nearest elastomer particle via the matrix was counted. Then, the proportion X (number %) of independently dispersed filler particles was calculated using the above formula (2).
[0127] [conditions] {device name} Schottky field emission scanning electron microscope JSM-F100 (manufactured by JEOL Ltd.) {Acceleration voltage} 3kV {magnification} 10,000x or 1,000x {Measurement range} 12.8μm×9.6μm (10,000x) or 128μm×96μm (1,000x) {Number of ratings} 10 areas / sample {Binarization and image analysis} ImageJ {Binarization method} MaxEntropy (The threshold value is adjusted appropriately so that only the filler particles can be separated by binarization. If binarization is not possible using image processing software, prepare an image in which only the filler particles are visually filled in using paint software, etc.)
[0128] The results of Examples 1 to 15 and Comparative Examples 1 to 3 are shown in Tables 5 and 6.
[0129] [Table 5]
[0130] [Table 6]
[0131] The particle sizes of the filler particles and the elastomer particles in Tables 5 and 6 were measured from SEM images of the cross sections, and the difference from the catalog values shown in Table 2 was within ±50%, and the SEM images of the cross sections confirmed that the measurement method was appropriate. In the examples, it was confirmed that two elastomer particles (3a, 3b) existing at an interval of 10 μm or less were dispersed apart from the filler particles in a 10,000x SEM image. In the examples, the proportion of independently dispersed elastomer particles (Y number %) is not significantly different from the proportion of independently dispersed filler particles (X number %), and can be 50 number % or more, and 70 number % or more. In a typical injection molded product, a surface portion (skin layer) and a central portion (core layer) can be formed on the test piece. In the examples, since the independent dispersion structure is ubiquitous over a wide area in the center (core layer) of the test piece, the ratios of the area occupancy of the matrix, the area occupancy of the filler particles, and the area occupancy of the elastomer particles are not significantly different from the composition ratios.
[0132] The resin compositions of Examples 1 to 15 are independently dispersed and exhibit a superior flexural modulus to the matrix alone shown in Table 1. In contrast, the resin compositions of Comparative Examples 1 to 3 have a core-shell structure and exhibit a lower flexural modulus than the matrix alone shown in Table 1.
[0133] Examples 1 to 3 and 11 are rated A for Charpy impact strength and flexural modulus, showing particularly excellent mechanical properties. In Examples 1 and 2, the elastomer material is D-1 containing an ester bond, which is a polar group, and therefore it is presumed that the Charpy impact strength is higher than that of Example 7, in which the elastomer material is D-7 containing no ester bond. In Examples 1 and 2, the particle diameter of the filler particles is 0.5 μm, which is smaller than that of Example 9, in which the particle diameter of the filler particles is 15.0 μm, and therefore it is presumed that the phenomenon described using FIG. 3(a) is suppressed, and the Charpy impact strength is higher than that of Example 9. In Example 7, the particle diameter of the filler particles is 0.5 μm, which is larger than that of Example 10, in which the particle diameter of the filler particles is 0.2 μm, and therefore it is presumed that the phenomenon described using FIG. 3(b) is suppressed, and the Charpy impact strength is higher than that of Example 10.
[0134] Examples 16 to 20, Comparative Example 4 Materials used in the present examples (including comparative examples) other than those shown in Tables 1 to 4 are as shown in Table 7. The fiber diameter and fiber length of the filler (glass fiber) shown in Table 7 are the values in the product catalog.
[0135] [Table 7]
[0136] The pellet production and molding in Examples 16 to 20 and Comparative Example 4 were the same as in Examples 1 to 15, except for the differences in the components.
[0137] In Examples 16 to 19, the matrix material A-1, the glass fibers of the filler particles B-7 to B-9, and the elastomer material D-1 were each fed by a weight feeder to a predetermined mass ratio. Prior to this feeding, the glass fibers of the filler particles B-7 to B-9 were treated with the surface treatment agent C-1 in the same manner as in the surface treatment described above.
[0138] In Example 20, the matrix material A-1, the glass fiber of the filler particle B-7, the elastomer material D-10, and the additive (flame retardant) E-1 were each fed by a weight feeder to a predetermined mass ratio. Before this feeding, the glass fiber of the filler particle B-7 was treated with the surface treatment agent C-4 in the same manner as the above-mentioned surface treatment. Before this feeding, the particles of the additive (flame retardant) E-1 were treated with the surface treatment agent C-1 in the same manner as the above-mentioned surface treatment.
[0139] In Comparative Example 4, the matrix material A-1, the glass fiber of the filler particle B-7, and the elastomer material D-9 were each fed by a weight feeder at a predetermined mass ratio. Prior to this feeding, the glass fiber of the filler particle B-7 was treated with the surface treatment agent C-1 in the same manner as in the above-mentioned surface treatment.
[0140] <Aspect ratio measurement> The center of the molded rectangular test piece was cut out and heat-treated at 450°C in a nitrogen atmosphere for 10 hours to remove components other than the filler particles. After that, observation was performed using a scanning electron microscope (SEM) under the conditions shown below to obtain a cross-sectional SEM image. Note that, depending on the length of the filler particles, the observation was performed at a magnification of 10,000 times when the observation magnification length was 5 μm or less, and at a magnification of 1,000 times when the length exceeded 5 μm. Furthermore, when the length of the filler particles exceeded 100 μm, the filler particles were divided into multiple SEM images to obtain an SIM image of the entire filler particle. From the obtained SEM image, the average value of the aspect ratio in any range of the SEM image obtained by binarization and image analysis under the conditions shown below was used as the aspect ratio of the filler particles. Note that the binarization and image analysis of the SEM images were performed using the image processing software ImageJ (available from https: / / imagej.nih.gov / ij / ) from the National Institutes of Health.
[0141] [conditions] {device name} Schottky field emission scanning electron microscope JSM-F100 (manufactured by JEOL Ltd.) {Acceleration voltage} 3kV {magnification} 10,000x or 1,000x {Measurement range} 12.8μm×9.6μm (10,000x) or 128μm×96μm (1,000x) {Number of ratings} 10 areas / sample {Binarization and image analysis} ImageJ {Binarization method} MaxEntropy (The threshold value is adjusted appropriately so that the filler particles can be separated by binarization. If binarization is not possible using image processing software, prepare an image in which only the filler particles are visually filled in using paint software, etc.) {How to calculate aspect ratio} The maximum diameter of a filler particle measured so as to pass through the center of gravity of the filler particle is defined as the filler particle length, and the diameter measured so as to pass through the center of gravity of the filler particle in a direction perpendicular to the maximum diameter is defined as the filler particle diameter. The aspect ratio of each filler particle is determined by dividing the filler particle length by the filler particle diameter, and the average value is calculated.
[0142] The results of Examples 16 to 20 and Comparative Example 4 are shown in Table 8.
[0143] [Table 8]
[0144] The ΔHSP value of the flame retardant and elastomer material is shown as "ΔHSP value 4", and the ΔHSP value of the matrix material and flame retardant is shown as "ΔHSP value 5" in Table 8.
[0145] By kneading the resin composition, the glass fibers are cut, and the fiber length of the filler particles 2 in the resin composition becomes shorter than the value shown in Table 7. The fiber lengths and aspect ratios of the glass fibers as filler particles in the resin compositions in Examples 16 to 20 and Comparative Example 4 are shown in Table 8. The fiber diameter of the glass fibers as filler particles does not change before and after kneading, and remains the fiber diameter shown in Table 7.
[0146] In the resin compositions of Examples 16 to 20, the filler particles and the elastomer particles have an independent dispersion structure, and the resin compositions show a flexural modulus superior to that of the matrix material A-1 alone shown in Table 1. In contrast, in the resin composition of Comparative Example 4, the filler particles and the elastomer particles have an adherent dispersion structure as shown in FIG. 2(c), and Comparative Example 4 has a lower flexural modulus than the other Examples. In the resin composition of Example 20, as shown in FIG. 2(b), flame retardant particles corresponding to additive particles 8 are dispersed in elastomer particles, and additive particles 8 and elastomer particles have a core-shell structure, and excellent flame retardancy can be obtained.
[0147] The present invention is not limited to the above-described embodiments and examples, and many modifications are possible within the technical concept of the present invention. Furthermore, the effects described in the embodiments and examples of the present invention are merely a list of the most preferable effects resulting from the present invention, and the effects of the present invention are not limited to those described in the embodiments and examples.
[0148] In addition, new matters may be added to at least one embodiment. The disclosure of this specification includes not only what is explicitly described in this specification, but also all matters that can be understood from this specification and the drawings attached to this specification.
[0149] In addition, in the specific numerical ranges exemplified in this specification, the description e to f (e and f are numbers) means e or more and / or f or less. In addition, in the specific numerical ranges exemplified, when a range of i to j and a range of m to n are both written (i, j, m, and n are numbers), the pair of lower limit and upper limit is not limited to the pair of i and j or the pair of m and n. For example, a combination of lower limit and upper limit of multiple pairs may be considered. That is, in the case where a range of i to j and a range of m to n are both written, the range of i to n may be considered or the range of m to j may be considered within a range that does not cause a contradiction. In addition, being e or more means e or larger than e (exceeding e), and a value larger than e may be adopted without adopting e. In addition, being f or less means f or smaller than f (less than f), and a value smaller than f may be adopted without adopting f.
[0150] Furthermore, the disclosure of this specification includes the complement of each concept described in this specification. In other words, if this specification contains a statement that "A is B," for example, it can be said that this specification discloses "A is not B" even if the statement that "A is not B" is omitted. This is because when a statement that "A is B" is made, it is assumed that the case in which "A is not B" is taken into consideration.
[0151] ≪Included components≫ The disclosure of this embodiment includes the following configuration. (Configuration 1) A resin composition comprising a matrix mainly composed of a polar polymer, a plurality of filler particles mainly composed of an inorganic material and having a particle diameter of 0.1 μm or more, and a plurality of elastomer particles each having a particle diameter of 0.1 μm or more, the plurality of filler particles and the plurality of elastomer particles are in contact with the matrix and dispersed in the matrix, In a cross section of the resin composition, a first elastomer particle and a second elastomer particle among the plurality of elastomer particles are present at an interval of 10 μm or less, Among the plurality of filler particles, a first filler particle that is closest to the first elastomer particle in the cross section is separated from the first elastomer particle via the matrix, A resin composition characterized in that, among the plurality of filler particles, a second filler particle that is closest to the second elastomer particle in the cross section is separated from the second elastomer particle via the matrix. (Configuration 2) The resin composition according to configuration 1, characterized in that the distance between the first filler particles and the second filler particles is 100 μm or less, the distance between the first filler particles and the first elastomer particles is 10 μm or less, and the distance between the second filler particles and the second elastomer particles is 10 μm or less. (Configuration 3) 10 of the cross sections 2 μm 2 Greater than or equal to 1000 2 μm 2 50% or more by number of the 10 or more filler particles in the following area range are separated from the plurality of elastomer particles via the matrix; 10 of the cross sections 2 μm 2 Greater than or equal to 1000 2 μm 250% or more by number of the 10 or more elastomer particles in the following area range are separated from the plurality of filler particles via the matrix; 3. The resin composition according to claim 1 or 2, which satisfies at least one of the above requirements. (Configuration 4) The cross-section of 10 particles including the first elastomer particles, the second elastomer particles, the first filler particles, and the second filler particles. 2 μm 2 Greater than or equal to 1000 2 μm 2 The occupancy rate in the following area ranges is: A resin composition according to any one of configurations 1 to 3, characterized in that the matrix is 30 area % or more and 90 area % or less, the plurality of filler particles is 1 area % or more and 50 area % or less, and the plurality of elastomer particles is 1 area % or more and 50 area % or less. (Configuration 5) The first elastomer particles, the second elastomer particles, the first filler particles, and the second filler particles in the resin composition are mixed. 3 μm 3 More than 1mm 3 The composition in the following volume range is 5. A resin composition according to any one of configurations 1 to 4, characterized in that the matrix is 30% by mass or more and 90% by mass or less, the plurality of filler particles is 1% by mass or more and 50% by mass or less, and the elastomer material constituting the plurality of elastomer particles is 1% by mass or more and 50% by mass or less.
[0152] (Configuration 6) 6. The resin composition according to any one of claims 1 to 5, wherein the elastomer material constituting the plurality of elastomer particles has a polar group. (Configuration 7) The resin composition according to any one of configurations 1 to 6, wherein the elastomer material constituting the plurality of elastomer particles has an ester bond. (Configuration 8) The resin composition according to any one of configurations 1 to 7, wherein the elastomer material constituting the plurality of elastomer particles has a Shore A hardness of 70 degrees or more. (Configuration 9) The resin composition according to any one of configurations 1 to 8, wherein the elastomer material constituting the plurality of elastomer particles is a thermoplastic elastomer. (Configuration 10) The resin composition according to any one of configurations 1 to 9, wherein the elastomer material constituting the plurality of elastomer particles is an acrylic elastomer or an ester elastomer. (Configuration 11) 11. The resin composition according to any one of configurations 1 to 10, wherein the melting point of the elastomer material constituting the plurality of elastomer particles is lower than the glass transition point or melting point of the matrix.
[0153] (Configuration 12) The ΔHSP value of the elastomer material constituting the surfaces of the plurality of filler particles and the plurality of elastomer particles is 7.0 MPa 1 / 2 12. The resin composition according to any one of configurations 1 to 11, characterized in that: (Configuration 13) 13. The resin composition according to any one of claims 1 to 12, wherein the particle diameter of the first elastomer particles and the second elastomer particles is 10 μm or less. (Configuration 14) 14. The resin composition according to any one of claims 1 to 13, wherein the particle diameters of the first elastomer particles and the second elastomer particles are 0.5 μm or more and 5 μm or less. (Configuration 15) 15. The resin composition according to any one of configurations 1 to 14, wherein the particle diameters of the first filler particles and the second filler particles are 10 μm or less. (Configuration 16) 16. The resin composition according to any one of configurations 1 to 15, wherein the particle diameters of the first filler particles and the second filler particles are 0.2 μm or more and 5 μm or less. (Configuration 17) 17. The resin composition according to any one of configurations 1 to 16, wherein at least one of the first filler particles and the second filler particles has a particle diameter of 2 μm or more. (Configuration 18) 18. The resin composition according to any one of claims 1 to 17, wherein the first filler particles and the second filler particles contain silica or calcium carbonate. (Configuration 19) 19. The resin composition according to any one of configurations 1 to 18, wherein the first filler particles and the second filler particles are fibrous. (Configuration 20) 20. The resin composition according to any one of configurations 1 to 19, wherein the first filler particles and the second filler particles have an aspect ratio of 5 or more and 100 or less. (Configuration 21) 21. The resin composition according to any one of claims 1 to 20, wherein the first filler particles and the second filler particles contain glass fibers or carbon fibers. (Configuration 22) 22. The resin composition according to any one of claims 1 to 21, further comprising dispersed particles in the elastomer particles. (Configuration 23) 23. The resin composition according to claim 22, wherein the particles dispersed in the elastomer particles contain a phosphorus compound and / or a flame retardant. (Configuration 24) 24. The resin composition according to any one of configurations 1 to 23, wherein the plurality of filler particles have a surface layer formed by surface treatment of a base made of the inorganic material. (Configuration 25) 25. The resin composition according to claim 24, wherein the surface treatment is a surface treatment with a silane coupling agent.
[0154] (Configuration 26) 26. The resin composition according to any one of claims 1 to 25, wherein the polar polymer is a polyester. (Configuration 27) 27. The resin composition according to any one of claims 1 to 26, wherein the polar polymer is polyethylene terephthalate. (Configuration 28) 28. The resin composition according to any one of claims 1 to 27, wherein the polar polymer has a carbodiimide group. (Configuration 29) The resin composition according to any one of structures 1 to 28, further comprising at least one of a metal material containing a transition metal element, a compound material containing a transition metal element, a metal material containing a typical metal element, and a compound material containing a typical metal element, which are different from the inorganic material that is the main component of the first filler particles.
[0155] (Configuration 30) 30. A method for producing a resin composition according to any one of Structures 1 to 29, comprising melt-kneading the matrix, the filler particles, and an elastomer material constituting the elastomer particles. (Configuration 31) 30. A pellet comprising the resin composition according to any one of claims 1 to 29. (Configuration 32) 30. A molded article comprising the resin composition according to any one of claims 1 to 29, wherein the polar polymer is a crystalline polymer. (Configuration 33) 30. An injection-molded article comprising the resin composition according to any one of claims 1 to 29. (Configuration 34) A member obtained by molding a resin composition according to any one of configurations 1 to 29, An apparatus comprising at least one of an electrical component, a metal component, and an optical component. (Configuration 35) 35. The device of claim 34, wherein the member is an exterior body. [Explanation of symbols]
[0156] 1: matrix, 2: filler particles, 3: elastomer particles, 4: elastomer material, 5: crazes, 6: cracks
Claims
1. A resin composition comprising a matrix mainly composed of a polar polymer, a plurality of filler particles mainly composed of an inorganic material and having a particle diameter of 0.1 μm or more, and a plurality of elastomer particles each having a particle diameter of 0.1 μm or more, the plurality of filler particles and the plurality of elastomer particles are in contact with the matrix and dispersed in the matrix, In a cross section of the resin composition, a first elastomer particle and a second elastomer particle among the plurality of elastomer particles are present at an interval of 10 μm or less, Among the plurality of filler particles, a first filler particle that is present closest to the first elastomer particle in the cross section is separated from the first elastomer particle via the matrix, A resin composition characterized in that, among the plurality of filler particles, a second filler particle that is closest to the second elastomer particle in the cross section is separated from the second elastomer particle via the matrix.
2. The resin composition according to claim 1, characterized in that the distance between the first filler particles and the second filler particles is 100 μm or less, the distance between the first filler particles and the first elastomer particles is 10 μm or less, and the distance between the second filler particles and the second elastomer particles is 10 μm or less.
3. 10 of the cross section 2 μm 2 Greater than or equal to 1000 2 μm 2 50% or more by number of the 10 or more filler particles in the following area range are separated from the plurality of elastomer particles via the matrix; 10 of the cross section 2 μm 2 Greater than or equal to 1000 2 μm 2 50% or more by number of the 10 or more elastomer particles in the following area range are separated from the plurality of filler particles via the matrix; The resin composition according to claim 1, which satisfies at least one of the above requirements.
4. The cross-section of the first elastomer particles, the second elastomer particles, the first filler particles, and the second filler particles. 2 μm 2 Greater than or equal to 1000 2 μm 2 The occupancy rate in the following area ranges is: The resin composition according to claim 1, characterized in that the matrix is 30 area % or more and 90 area % or less, the plurality of filler particles is 1 area % or more and 50 area % or less, and the plurality of elastomer particles is 1 area % or more and 50 area % or less.
5. The resin composition contains the first elastomer particles, the second elastomer particles, the first filler particles, and the second filler particles, and the total weight of the first elastomer particles, the second elastomer particles, the first filler particles, and the second filler particles. 3 μm 3 More than 1mm 3 The composition in the following volume range is The resin composition according to claim 1, characterized in that the matrix is 30% by mass or more and 90% by mass or less, the plurality of filler particles is 1% by mass or more and 50% by mass or less, and the elastomer material constituting the plurality of elastomer particles is 1% by mass or more and 50% by mass or less.
6. 6. The resin composition according to claim 1, wherein the elastomer material constituting the plurality of elastomer particles has a polar group.
7. 6. The resin composition according to claim 1, wherein the elastomer material constituting the plurality of elastomer particles has an ester bond.
8. 6. The resin composition according to claim 1, wherein the elastomer material constituting the plurality of elastomer particles has a Shore A hardness of 70 degrees or more.
9. 6. The resin composition according to claim 1, wherein the elastomer material constituting the plurality of elastomer particles is a thermoplastic elastomer.
10. 6. The resin composition according to claim 1, wherein the elastomer material constituting the plurality of elastomer particles is an acrylic elastomer or an ester elastomer.
11. 6. The resin composition according to claim 1, wherein a melting point of an elastomer material constituting the plurality of elastomer particles is lower than a glass transition point or a melting point of the matrix.
12. The ΔHSP value of the elastomer material constituting the surfaces of the plurality of filler particles and the plurality of elastomer particles is 7.0 MPa. 1 / 2 The resin composition according to any one of claims 1 to 5, characterized in that
13. 6. The resin composition according to claim 1, wherein the first elastomer particles and the second elastomer particles have a particle size of 10 μm or less.
14. 6. The resin composition according to claim 1, wherein the particle diameter of the first elastomer particles and the second elastomer particles is 0.5 μm or more and 5 μm or less.
15. 6. The resin composition according to claim 1, wherein the first filler particles and the second filler particles have a particle size of 10 μm or less.
16. 6. The resin composition according to claim 1, wherein the first filler particles and the second filler particles have a particle size of 0.2 μm or more and 5 μm or less.
17. 6. The resin composition according to claim 1, wherein at least one of the first filler particles and the second filler particles has a particle diameter of 2 μm or more.
18. 6. The resin composition according to claim 1, wherein the first filler particles and the second filler particles contain silica or calcium carbonate.
19. 6. The resin composition according to claim 1, wherein the first filler particles and the second filler particles are fibrous.
20. 6. The resin composition according to claim 1, wherein the first filler particles and the second filler particles have an aspect ratio of 5 or more and 100 or less.
21. 6. The resin composition according to claim 1, wherein the first filler particles and the second filler particles contain glass fibers or carbon fibers.
22. 6. The resin composition according to claim 1, further comprising dispersed particles in the elastomer particles.
23. 23. The resin composition according to claim 22, wherein the particles dispersed in the elastomer particles contain a phosphorus compound and / or a flame retardant.
24. 6. The resin composition according to claim 1, wherein the plurality of filler particles have a surface layer formed by surface treatment of the base made of the inorganic material.
25. 25. The resin composition according to claim 24, wherein the surface treatment is a surface treatment with a silane coupling agent.
26. 6. The resin composition according to claim 1, wherein the polar polymer is a polyester.
27. 6. The resin composition according to claim 1, wherein the polar polymer is polyethylene terephthalate.
28. The resin composition according to claim 1 , wherein the polar polymer has a carbodiimide group.
29. The resin composition according to any one of claims 1 to 5, characterized in that it contains at least one of a metal material containing a transition metal element, a compound material containing a transition metal element, a metal material containing a typical metal element, and a compound material containing a typical metal element, which are different from the inorganic material that is the main component of the first filler particles.
30. The method for producing a resin composition according to claim 1 , further comprising a step of melt-kneading the matrix, the filler particles, and an elastomer material constituting the elastomer particles.
31. A pellet comprising the resin composition according to claim 1 .
32. A molded article comprising the resin composition according to claim 1 , wherein the polar polymer is a crystalline polymer.
33. An injection-molded article comprising the resin composition according to any one of claims 1 to 5.
34. A member obtained by molding the resin composition according to any one of claims 1 to 5; An apparatus comprising at least one of an electrical component, a metal component, and an optical component.
35. 35. The device of claim 34, wherein the member is an exterior body.
Citation Information
Patent Citations
Resin composition, method for producing resin composition and information processing device
JP2020193284A